Implementasi Hukum Personal Guarantee dalam Praktik Kepailitan - Nadriana, Lenny; Ikhwansyah, Isis (Pagaruyuang Law Journal, 2018)
Various judgments of bankruptcy petition declare a Guarantor that Guarantor may be made bankrupt, so that the guarantor as referred to in Article 1 paragraph 1 of the Bankruptcy Law must give up all his property to be public enclosures to pay off the creditors' payment. Legal Position of Corporate Guarantor or Personal Guarantee which is used as a bankrupt debtor is the same as the main debitor because at the time of execution of the deed of guarantee guarantee is willing to voluntarily give up all his privileges without waiting for the main debtor of default and hartan sold. Regarding the making of the Security Guarantee Coverage the position of the guarantor that may be made bankrupt is a weak position in an agreement, so the role of the notary must be able to provide legal counseling prior to the signing of the guarantee deins held by the Guarantor Personal Guarantor or Corporate Guarantor.